2017
DOI: 10.1111/joa.12768
|View full text |Cite
|
Sign up to set email alerts
|

The clustering and morphology of chondrocytes in normal and mildly degenerate human femoral head cartilage studied by confocal laser scanning microscopy

Abstract: Chondrocytes are the major cell type present in hyaline cartilage and they play a crucial role in maintaining the mechanical resilience of the tissue through a balance of the synthesis and breakdown of extracellular matrix macromolecules. Histological assessment of cartilage suggests that articular chondrocytes in situ typically occur singly and demonstrate a rounded/elliptical morphology. However, there are suggestions that their grouping and fine shape is more complex and that these change with cartilage deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 49 publications
3
46
0
Order By: Relevance
“…Full-depth osteochondral explants from human femoral heads obtained from femoral neck fracture with ethical permission and patient consent, were incubated with CMFDA (5-chloromethyl-fluorescein diacetate) and propidium iodide (10 μM each), prepared for confocal scanning laser microscopy (CLSM) and imaged in the axial direction (i.e. viewed down onto the cartilage surface using a × 40 0.8 NA water-immersion lens) as described [27 •]. Chondrocytes are labelled green or red for living or dead cells, respectively.…”
Section: A New Look At Cartilage—imaging In Situ Fluorescently-labellmentioning
confidence: 99%
See 2 more Smart Citations
“…Full-depth osteochondral explants from human femoral heads obtained from femoral neck fracture with ethical permission and patient consent, were incubated with CMFDA (5-chloromethyl-fluorescein diacetate) and propidium iodide (10 μM each), prepared for confocal scanning laser microscopy (CLSM) and imaged in the axial direction (i.e. viewed down onto the cartilage surface using a × 40 0.8 NA water-immersion lens) as described [27 •]. Chondrocytes are labelled green or red for living or dead cells, respectively.…”
Section: A New Look At Cartilage—imaging In Situ Fluorescently-labellmentioning
confidence: 99%
“…Chondrocytes are labelled green or red for living or dead cells, respectively. Representative images of chondrocyte morphology are taken from images in Karim et al [27 •] The scale bar shown in (a) is the same for all panels …”
Section: A New Look At Cartilage—imaging In Situ Fluorescently-labellmentioning
confidence: 99%
See 1 more Smart Citation
“…Chondrocyte clustering is a histological sign of late-stage OA [1,37]; this type of clustering and its associated morphological abnormalities are particularly evident in the superficial zones of OA tissues. To explore whether p47phox was associated with ROS production and cartilage damage, samples of degenerating articular cartilage from patients with OA were assessed.…”
Section: P47phox and Ros Were Highly Expressed In Chondrocyte Clustermentioning
confidence: 99%
“…Since chondrocytes are of mesenchymal origin, it might be possible, that they leave their tissue speci c position and migrate to the periphery of the tissue, but in our setting CLSM showed highly conserved cell architecture inside the tissue (21). Cartilage is divided into three different cellular zones: The super cial zone (tightly packed with MSC like cells), the mid zone (pearl-bead-like alignment) and the deep zone (column-like chondrocyte alignment) (22) (23). The conservation of the cellular zones depends on the supply with nutrients and physiological cartilage infrastructure -minimizing cellular stress by malnutrition and/or hypoxia (24).…”
Section: Discussionmentioning
confidence: 75%